2022
DOI: 10.3390/app12030994
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Knee Joint Effusion—A New Dimension of Laboratory Diagnostics

Abstract: Joint effusions are most frequently caused by osteoarthritis, trauma, an infection process or an autoimmune disease. The development of joint effusion due to a tumor process is rare but should be taken into consideration in the diagnostics. Joint effusions are examined mostly by means of microbiology to rule out or confirm pyogenic synovitis. These standard processes may take up to several days. The article presented here describes a unique case of a 74-year-old female diagnosed with a generalized malignant pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…In addition, the normal level of uric acid indicated that there were no gout alterations. A cytological‐energy analysis of the SF can also be used in the diagnostic process, for typing the tumor and for accelerating the start of treatment 6 . There are also case reports in the literature of reactive arthritis developing during or after COVID‐19 infection 12–14 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the normal level of uric acid indicated that there were no gout alterations. A cytological‐energy analysis of the SF can also be used in the diagnostic process, for typing the tumor and for accelerating the start of treatment 6 . There are also case reports in the literature of reactive arthritis developing during or after COVID‐19 infection 12–14 …”
Section: Discussionmentioning
confidence: 99%
“…The aerobic metabolism in the SF is determined by the coefficient of energy balance (KEB). In the first SF sample area the aerobic metabolism with KEB = 34.1 reliably excluded the purulent type of inflammation induced by extracellular bacteria 5,6 . The analysis of the second SF sample manifested a decrease in the cell count (360/1 μL) and a significant decrease in neutrophils (percentage of neutrophils = 6.0%; percentage of lymphocytes = 71.0%; percentage of monocytes = 23.0%) (Figure 3).…”
Section: Case Presentationmentioning
confidence: 98%
See 3 more Smart Citations